Non-classical phenotypes of mismatch repair deficiency and microsatellite instability in primary and metastatic tumors at different sites in Lynch syndrome - Li, Zhiyu; Cheng, Bo; Liu, Shan; Ding, Shanshan; Liu, Jinhong; Quan, Lanju; Hao, Yanjiao; Xu, Lin; Zhao, Huan; Guo, Jing; Sun, Suozhu (Frontiers in Oncology, 2022)
Abstract Background: Lynch syndrome is a genetic disease characterized by abnormal DNA replication caused by germline mutations in the mismatch repair (MMR) gene. There are rare non-classical phenotypes with loss of MMR protein expression and inconsistent microsatellite stability (MSS) in Lynch syndrome-related tumors. However, the difference between microsatellite instability (MSI) of intestinal and extraintestinal tumors in a patient with Lynch syndrome has not been reported. Herein, we reported the non-classical phenotypes of mismatch repair deficiency (dMMR) and MSI in four types of Lynch syndrome in patients with colorectal cancer and other primary and metastatic tumors. Methods: A retrospective analysis was conducted on four patients diagnosed with Lynch syndrome between 2018 and 2022 in the Department of Pathology of the Rocket Forces Specialized Medical Center. A one-step immunohistochemical (IHC) assay was employed to detect loss in the expression of Lynch syndrome-associated MMR proteins (MLH1, PMS2, MSH2, and MSH6). MSI detection was performed in both primary and metastatic tumors at different sites in the four patients using NCI 2B3D (BAT25, BAT26, D2S123, D17S250, and D5S346) and single nucleotide site (BAT25, BAT26, NR21, NR24, NR27, and MONO27) methods. In addition, related MMR gene germline mutations, somatic mutations, and MLH1 gene promoter methylation were analyzed using next-generation sequencing and TaqMan probe-based methylation-specific polymerase chain reaction (MethyLight). Results: Two of the four patients were heterozygous for MSH6 germline pathogenic mutations, and the other two were heterozygous for MSH2 germline pathogenic mutations. In all cases, IHC detection of protein expression of the MMR gene with germline mutations was negative in all primary and metastatic tumors; non-classical phenotypes of dMMR and MSI were present between primary and metastatic tumors at different sites. dMMR in Lynch colorectal cancer demonstrated high MSI, whereas MSI in primary and metastatic tumors outside the intestine mostly exhibited MSS or low MSI. Conclusions: The non-classical dMMR and MSI phenotype are mostly observed in Lynch syndrome, even in the context of MMR protein expression loss. Extraintestinal tumors infrequently present with a high degree of MSI and often exhibit a stable or low degree of MSI.